2019
DOI: 10.4012/dmj.2018-307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of composition and powder/water ratio on adhesion strength and initial viscosity of powder-type denture adhesives based on CMC-Na and PVM-MA

Abstract: We evaluated the influence of the composition and powder/water (P/W) ratio of powder-type denture adhesives (DA) based on sodium carboxymethyl cellulose (CMC-Na) and poly(methyl vinyl ether-maleic anhydride) (PVM-MA) on the strength of adhesion to acrylic resin and initial viscosity. Twenty types of DA were prepared by mixing CMC-Na and PVM-MA at various weight ratios with distilled water in P/W ratios ranging from 0.125 to 0.500. Adhesion strength and viscosity were measured using a universal testing machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Bioadhesive polymers are often used for controlling release of medical and dental therapeutic agents. PVM/MA copolymer has been widely used in dentistry [ 17 , 21 23 ], and its bioadhesive properties are related to the formation of carboxylic groups from the polyanhydride residues of the copolymer [ 24 ]. It has been shown that dentifrice containing PVM/MA copolymers could improve the retention of fluoride after a single brushing application compared to those without bioadhesive copolymers[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioadhesive polymers are often used for controlling release of medical and dental therapeutic agents. PVM/MA copolymer has been widely used in dentistry [ 17 , 21 23 ], and its bioadhesive properties are related to the formation of carboxylic groups from the polyanhydride residues of the copolymer [ 24 ]. It has been shown that dentifrice containing PVM/MA copolymers could improve the retention of fluoride after a single brushing application compared to those without bioadhesive copolymers[ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyvinyl methyl ether / maleic acid (PVM/MA) copolymer is a widely used bioadhesive molecule. Its tissue adhesion characters have been utilized in denture adhesives [ 17 ], anti-gingivitis or desensitizing mouthwashes [ 10 , 18 ]. When combined with inorganic fillers, PVM/MA performed better in dentine tubule occlusion than products that contained either the fillers or the copolymers alone [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A liner type (cushion form) denture adhesive consists of a non-aqueous paste of polyvinyl acetate and ethyl alcohol, and it improves the retention and stability by filling the gap between the denture intaglio surface of ill-fitting dentures and the basal seat mucosa [7]. Generally, the use of both powder-and cream-type denture adhesives, rather than the liner type, is recommended for clinical cases, because both powder-and cream-type denture adhesives produce a thin layer of denture adhesive while minimally changing the occlusal relationship after application [8].…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of the antimicrobials, such as sodium borate, sodium tetraborate, hexachlorophene or propyl hydroxybenzoate, is to prevent the appearance of Candida Albicans fungal infections because some studies have shown that the use of denture adhesives increased its growth 3,7 . Finally, the additives that serve as fillers, such as magnesium oxide, in addition to moistening, are intended to impart a pleasant taste for the user (e.g., mint or gaultheria oil) 8,9 …”
mentioning
confidence: 99%
“…3,7 Finally, the additives that serve as fillers, such as magnesium oxide, in addition to moistening, are intended to impart a pleasant taste for the user (e.g., mint or gaultheria oil). 8,9 Denture adhesives are sold both as creams and powders. 10 This study was focused on the use of cream format adhesives because they have more bond strength and the time in contact with the oral mucosa is longer than in the case of a powder.…”
mentioning
confidence: 99%